Polynuclear Nickel Hexacyanoferrate/Graphitized Mesoporous Carbon Hybrid Chemically Modified Electrode for Selective Hydrazine Detection - Palani Barathi; Annamalai Senthil Kumar; Minnal Ranjan Babu Karthick (International Journal of Electrochemistry)
A hybrid polynuclear nickel hexacyanoferrate (NiHCFe)/graphitized mesoporous carbon- (GMC-) modified glassy carbon electrode (GCE/NiHCFe@GMC) has been prepared by a sequential method using electrodeposited Ni on a GMC-modified glassy carbon electrode (GCE/Ni@GMC) as a template and [Fe(CN)6]3− as an in-situ chemical precipitant, without any additional interlinking agent. Physicochemical and electrochemical characterizations reveal the presence of NiHCFe units within the porous sites of the GMC. The GCE/NiHCFe@GMC electrode showed highly stable and well-defined redox behaviors with surface-confined electron-transfer mechanism in a pH 7 phosphate buffer solution. The GCE/NiHCFe@GMC showed about 20 times enhancement in hydrazine oxidation peak current along with 500 mV reduction in overpotential over the corresponding unmodified GCE/GMC. Hydrazine calibration plots by CV and amperometric i-t methods were linear up to 1 mM and 220 μM with current sensitivity values of 15.86 μA/mM and 7.37 nA/μM, respectively. Calculated detection limit by the amperometric i-t method was 23.2 nM. The hybrid GCE/NiHCFe@GMC exhibits remarkable tolerance to important industrial and biological interferents. Finally determination of hydrazine in cigarette smoke sample was successfully demonstrated.